Does the development of the digital economy improve carbon emission efficiency? - Han, Jun; Jiang, Tianhe (Frontiers in Ecology and Evolution, 2022)
The improvement of carbon emission efficiency is guided by high-quality economic development, and the organic integration of ecology and economy is an important goal of putting sustainable economic development into action. Based on China's provincial panel data from 2008 to 2019, this article constructs a digital economy development index from the perspective of the digital economy and analyzes its impacts on carbon emission efficiency. The conclusion is that the development of the digital economy has significantly improved carbon emission efficiency. Through the analysis of the spatial spillover effect, it is found that regional carbon emission efficiency has a spatial correlation, but the development of the digital economy has no significant impact on the carbon emission efficiency of neighboring regions. Industrial structure adjustment, the energy structure, and technological progress are further analyzed as three mechanisms affecting carbon emission efficiency. It is found that the quality of industrial structure adjustment significantly promotes the improvement of carbon emission efficiency, while the energy structure significantly inhibits its improvement, and the range of industrial structure adjustment and technological progress have no significant impact on carbon emission efficiency. Based on the threshold effect, carbon emission efficiency be promoted only when the energy structure is in the interval unit (0.1288, 0.2441) and technological progress is >1.0591. Based on the above conclusion, we put forward corresponding policy suggestions.